Efek Konsentrasi Logam Cu dalam Larutan Brine terhadap Pembentukan Warna Hijau pada Daging Tuna - Frans Gruber Ijong; Stevy Imelda M. Wodi (Jurnal Ilmiah Tindalung, 2015)
The effect of Cu-brine on the formation of green color on tuna meat canned was studied using AAS method. The result shows that of heating by sterilization process tends supported formation of bluegreeness color of tuna meat. Therefore, the more high Cu content in brine gave significant effect on the formation of blue-greeness color on tuna meat canned should be considered